2019
DOI: 10.1371/journal.pone.0219813
|View full text |Cite
|
Sign up to set email alerts
|

Addressing broader reproductive health needs of female sex workers through integrated family planning/ HIV prevention services: A non-randomized trial of a health-services intervention designed to improve uptake of family planning services in Kenya

Abstract: Background Despite considerable efforts to prevent HIV and other sexually transmitted infections (STI) among female sex workers (FSW), other sexual and reproductive health (SRH) needs, such preventing unintended pregnancies, among FSW have received far less attention. Programs targeting FSW with comprehensive, accessible services are needed to address their broader SRH needs. This study tested the effectiveness of an intervention to increase dual contraceptive method use to prevent STIs, HIV and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 27 publications
0
30
0
1
Order By: Relevance
“…Although there is growing evidence that integrated HIV and family planning delivery in a single location facilitates contraceptive uptake, 71,74,75 there are several considerations for implementation within existing community-based HIV services. There is empirical evidence that providing multiple contraceptive options improves uptake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is growing evidence that integrated HIV and family planning delivery in a single location facilitates contraceptive uptake, 71,74,75 there are several considerations for implementation within existing community-based HIV services. There is empirical evidence that providing multiple contraceptive options improves uptake.…”
Section: Discussionmentioning
confidence: 99%
“…76 Elsewhere, making longer-acting methods readily available to FSWs at a drop-in center alongside counseling on methods suited to a woman's needs and current fertility intentions significantly increased demand and uptake of effective contraceptives. 75 However, the predominance of lower cadres of health care workers and peer outreach workers who often staff community-led FSW services may limit the number of staff with specific training and skills for contraception administration, especially when considering voluntary LARCs. 77,78 Physical space with adequate privacy and space for an examination table required for LARC administration may also be limited in drop-in centers.…”
Section: Discussionmentioning
confidence: 99%
“…Expanding such community-based model which reaches out to FSWs in their areas of work, to further include family planning services can be an effective strategy to reduce unintended pregnancy among FSWs. There is a growing body of research suggesting that integration of HIV and family planning services in a single location as well as providing multiple contraceptive options suited for fertility intentions increase demand and uptake of contraceptives [18,[78][79][80]. One study in Uganda showed that FSWs were more likely to receive contraceptive services if they had accessed HIV testing [10].…”
Section: Discussionmentioning
confidence: 99%
“…Condom failure or condom breakage and non-use among FSWs are common because of physical or sexual violence and drug or alcohol intoxication during sex work [20][21][22][23]. Further, sex workers´ financial and emotional dependence to their partners undermine their autonomy to insist on the use of condom or make them forgo condom use for extra payment [4,18,[24][25][26][27], leading to unintended pregnancy [28,29]. Unintended pregnancies that result in live birth have socio-economic implications that may intensify HIV risk associated with sex work [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-two studies reported on this outcome [57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][78][79][80][81][82][83][84][85][86][87]89,90]. Fifty effect estimates from 27 studies were included in the meta-analysis ( Figure 3).…”
Section: Condom Usementioning
confidence: 99%